The n-Total Graph of an Integral Domain - Abi Habib, Myriam (2025)
A Master of Science thesis in Mathematics by Myriam Abi Habib entitled, “The n-Total Graph of an Integral Domain”, submitted in May 2025. Thesis advisor is Dr. Ayman Badawi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).